First Replication of the Involvement of OTUD6B in Intellectual Disability Syndrome With Seizures and Dysmorphic Features - Straniero, Letizia; Rimoldi, Valeria; Soldà, Giulia; Bellini, Melissa; Biasucci, Giacomo; Asselta, Rosanna; Duga, Stefano (Frontiers in Genetics, 2018)
Biallelic mutations in the ovarian tumor domain-containing 6B (OTUD6B) gene, coding for a deubiquitinating enzyme, were recently described to cause an intellectual disability syndrome characterized by seizures and dysmorphic features in 6 families worldwide. We here report on a 6-year-old Italian girl, presenting mild intellectual disability, speech and motor delay, and recurrent seizures, who came to our attention after being screened for genes responsible for Rubinstein-Taybi syndrome, Kabuki syndrome, and epilepsy. We hence submitted the proband’s DNA to whole-exome sequencing, disclosing two candidate heterozygous splicing mutations in the OTUD6B gene: c.324+1G>C and c.405+1G>A. Both variants are reported in the GnomAD database with a frequency lower than the 10-5 and affect the donor splicing site, of exon 2 and exon 3, respectively. Sanger sequencing confirmed the segregation of the variants in the family, showing that both parents are carriers of one mutation. RT-PCR experiments demonstrated that both variants affect OTUD6B splicing and lead to the production of aberrant transcripts, the major ones being, in both cases, the skipping of the upstream exon. Quantitative analysis performed by competitive-fluorescent RT-PCR on the patient RNA showed that the proband presents less than 1% of wild-type transcripts, further strengthening the causative role of these variants. This represents the first replication of the involvement of the OTUD6B gene in this syndrome and points to the appropriateness of screening OTUD6B in suspected Rubinstein-Taybi syndrome patients with negative results after the screening of the major genes.